Dengue Fever Case Management in Maros Regency, Indonesia - Kurniawati, Indah; Susilawaty, Andi; Habibi, Habibi; Amansyah, Munawir (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Dengue fever is blood bone disease which is transferred through dengue virus infected Aedes mosquitos spread commonly in tropical and sub-tropical areas across the world. This research aims to describe the management of dengue fever case eradication program in Maros Regency. It uses a descriptive qualitative method in scrutinizing the issue. The research samples consist of 22 informants who are selected using the purposive sampling technique. The findings indicate that the management of the dengue fever eradication program is divided into several divisions namely agent management, media management, host management, and case management. In this case, the agent management division is responsible in identifying dengue fever patients by utilizing Active Case Detection (ACD) and Passive Case Detection (PCD) methods. Furthermore, the program manages the vector control through Abate utilization, larva monitoring agent designation, and fogging. Environmental control is carried out through the 3M program (close, drain and bury) and house yard cleaning. In addition to that, the program also encourages dengue fever patients to do self-medication by increasing their thrombocyte level and reducing their hematocrit level. Overall, many stakeholders participate in the dengue fever eradication program in Maros Regency, including the Health Department of Maros, health centers across Maros, local government, as well as community members. Finally, this research recommends the Health Department of Maros improve the quality of Abate distribution to health centers across Maros Regency